Conjugated execution of maneuvers of defensive and counterattacking actions used by athletes in applied martial arts for training personnel to perform apprehension techniques - Zakharova, Yu.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the techniques of maneuvering of defensive and counterattacking actions used by athletes in the competitive activity of applied martial arts for training the personnel of the internal affairs bodies in the use of apprehension techniques. Methods and structure of the study. An analysis was carried out of information sources devoted to the problem of the conjugated execution of maneuvers of defensive and counterattacking actions used by athletes in applied martial arts. Results and conclusions. In the article, the author reveals the features of defensive and counterattacking actions against strikes performed by martial-arts athletes in competitive activity. The issues of technical actions for defense against punches, performed by sequential and combined actions for carrying out apprehension techniques, are considered. Tactical-technical actions of performing conjugated maneuvering, used by athletes in applied martial arts for performing defensive and counterattacking actions with the subsequent application of tactical preparations, are proposed.